Dexamethasone Modifies Cystatin C-Based Diagnosis of Acute Kidney Injury During Cisplatin-Based Chemotherapy - Timothy J. Pianta; John W. Pickering; Lena Succar; Melvin Chin; Trent Davidson; Nicholas A. Buckley; Fahim Mohamed; Zoltan H. Endre (Kidney & Blood Pressure Research, 2017)
Background/Aims: Plasma cystatin C (pCysC) may be superior to serum creatinine (sCr) as a surrogate of GFR. However, the performance of pCysC for diagnosing acute kidney injury (AKI) after cisplatin-based chemotherapy is potentially affected by accompanying corticosteroid anti-emetic therapy and hydration. Methods: In a prospective observational study pCysC, sCr, urinary kidney injury molecule-1 (KIM-1), and urinary clusterin were measured over 2 weeks in 27 patients given first-cycle chemotherapy. The same variables were measured over 2 weeks in Sprague–Dawley rats given a single intraperitoneal injection of dexamethasone, cisplatin, or both, and in controls. Results: In patients, pCysC increases were greater than sCr 41% vs. 16%, mean paired difference 25% (95% CI: 16–34%)], relative increases were ≥ 50% in 9 patients (35%) for pCysC compared with 2 (8%) for sCr (p = 0.04) and increases in sCr were accompanied by increased KIM-1 and clusterin excretion, but increases in pCysC alone were not. In rats, dexamethasone administration produced dose-dependent increases in pCysC (and augmented cisplatin-induced increases in pCysC), but did not augment histological injury, increases in sCr, or KIM-1 and clusterin excretion. Conclusions: In the presence of dexamethasone, elevation of pCysC does not reliably diagnose AKI after cisplatin-based chemotherapy.